Antibiotic-induced change of bacterial communities associated with the copepod Nitocra spinipes. - Anna Edlund (Public Library of Science (PLoS), 2012)
Environmental pressures, such as physical factors, diet and contaminants may affect interactions between microbial symbionts and their multicellular hosts. Despite obvious relevance, effects of antimicrobial contaminants on host-symbiont relations in non-target aquatic organisms are largely unknown. We show that exposure to antibiotics had negative effects on survival and juvenile development of the copepod Nitocra spinipes and caused significant alterations in copepod-associated bacterial communities. The significant positive correlations between indices of copepod development and bacterial diversity indicate that disruption of the microflora was likely to be an important factor behind retarded juvenile development in the experimental animals. Moreover, as evidenced by ribotype distribution in the bacterial clone libraries, the exposure to antibiotics caused a shift in dominance from Betaproteobacteria to Cardinium bacteria; the latter have been shown to cause reproductive manipulations in various terrestrial arthropods. Thus, in addition to providing evidence that the antibiotic-induced perturbation of the microbial community associates with reductions in fitness-related traits of the host, this study is the first record of a copepod serving as a host for endosymbiotic Cardinium. Taken together, our results suggest that (1) antimicrobial substances and possibly other stressors can affect micobiome and symbiont-mediated interactions in copepods and other hosts, and (2) Cardinium endosymbionts may occur in other copepods and affect reproduction of their hosts.